Secondary Education at the Crossroads International Perspectives Relevant to the Asia-Pacific Region - Hughes, Phillip (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2006)
Education is a universal priority. Currently, it is at a crossroad. In every society it is valued as a major road to produce more productive, more harmonious and healthier citizens. Yet, in every setting there is deep dissatisfaction with the overall performance of education and there are major moves towards reform, sometimes superficial but more often fundamental. These reform processes have had only moderate and very uneven success. Too often they are episodic, reflecting a short-term approach which is frequently changed for the latest enthusiasm or the most recent administration. In Asia and the Pacific countries many systems are in the process of construction or reconstruction. These issues and concerns are particularly true for secondary education which in many countries has become the weakest link in the education chain. Can we learn from the experiences of others when it comes to the reform of secondary education? Given the multiplicity of efforts at reform, and the variety of situations for reform, there may well be lessons we can learn from each other's efforts and each others failures and successes. This book features contributions from experienced researchers who have worked in many different settings and bring their own insights to attack this universal problem.